THE INFLUENCE OF ACTORS’ ONSCREEN ALCOHOL CONSUMPTION AND SMOKING ON THEIR FANS FROM SOCIAL LEARNING PERSPECTIVE - M, Venkates; M, Sripriya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In recent years, every movie has begun with the statutory warning saying, “Smoking Causes Cancer and Smoking Kills; Liquor Drinking is Injurious to Health." These statutory warnings are shown to the cinema audience to raise awareness that drinking and smoking are not socially accepted behaviours. This research aims to find out whether the actors’ on-screen alcohol consumption and smoking in films had an influence on their fans. The study was conducted between the period August 2023 to October 2023.This study adopted a quantitative method with purposive sampling technique and the responses were collected through a survey from 254 male respondents from the state of Tamil Nādu. The study has found that such as age and locality are found to have high influence on the behaviour change at 0.01 level, Besides the age, locality, educational qualification, and occupation has high chances of fans Imitation by watching films 0.01 level. The impact of age, locality, and educational qualification on reinforcement and self-efficacy has significant relationships at the 0.01 level of significance thus shows how fans support and oppose actors’ similar actions. Movie watching in theatre compared with self-efficacy does not have significant relationship because fans does not resist in influencing by watching their favourite actors. The findings revealed many significant associations and thus shows the relationship between movie-watching habits had influence on adoption of onscreen behaviours of their favourite actors. As a result, the representations of drinking and smoking by the actors have the potential to have a negative influence on fans health and lifestyle.